Gritty peers - Effrosyni Adamopoulou; Yaming Cao; Ezgi Kaya (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
We use the National Longitudinal Study of Adolescent to Adult Health to explore how high school peers' grit, a personality trait characterized by perseverance and passion, influences long-term outcomes approximately 15 years after high school. Exploiting random variation within schools across cohorts and the longitudinal nature of our data, we find t hat p eer g rit s ignificantly in creases fu ture earnings, especially for students from disadvantaged backgrounds. This implies that peer grit may help bridge socioeconomic gaps. We identify two key mechanisms: an increased likelihood of employment in jobs aligned with career goals and an increased resilience to difficulties. Additionally, peer grit leads to higher job satisfaction and asset accumulation. Thus, peer grit's effects extend beyond short-term educational performance and persist into adulthood.
Keywords: I24; J13; J24; 330; grit; peer effects; long-term outcomes; Add Health